To determine the solution of the system of equation.
Retired math prof. Very extensive Precalculus tutoring experience.
x2 - x - y = 11 and x - y = 2
From the second equation, y = x - 2.
Substitute for y in the other equation: x2 - x - (x - 2) = 11
So, x2 - 2x + 2 = 11
x2 - 2x - 9 = 0
Use the quadratic Formula to find x and then use the fact that y = x - 2 to get y.
Get a free answer to a quick problem.
Most questions answered within 4 hours.
Choose an expert and meet online.
No packages or subscriptions, pay only for the time you need.
Answers · 2
Answers · 4
Answers · 3